Tracking the Fatigue Status after a Resistance Exercise through Different Parameters - Brisola, Gabriel Motta Pinheiro [UNESP] (2022)
The purpose of the study was to investigate the sensitivity of back squat bar velocity, isometric mid-thigh pull, heart rate variability parameters, perceived recovery scale and step counts for tracking the muscular fatigue time-course (reduction in countermovement jump [CMJ] performance) after strenuous acute lower limb resistance exercise. Sixteen healthy men performed heart rate variability assessment, perceived recovery scale, CMJ, back squat bar velocity, isometric mid-thigh pull, and daily step counts before and 24 h, 48 h and 72 h post a strenuous acute lower limb resistance exercise (8×10 repetitions). The CMJ height decreased at 24 and 48 h after exercise session (p ≤0.017), evidencing the muscular fatigue. The perceived recovery scale presented lower values compared to baseline until 72 h after exercise session (p <0.001 for all). The heart rate variability parameters and step counts were not significantly different across time. At 24 h post, only mean force of mid-thigh pull was decreased (p =0.044), while at 48 h post, only peak force of mid-thigh pull was decreased (p =0.020). On the last day (72 h), only bar velocity (mean) presented reduction (p =0.022). Therefore, the perceived recovery scale was the only variable sensible to tracking muscular fatigue, i. e. presenting a similar time-course to CMJ height.